Estimation of household demand systems with theoretically compatible engel curves and unit value specifications - Ian Crawford; François Laisney; Ian Preston (Institute for Fiscal Studies (IFS), 2002)
We develop a method for estimation of price reactions using unit value data which exploits the implicit links between quantity and unit value choices. This allows us to combine appealing Engel curve specifications with a model of unit value determination in a way which is consistent with demand theory, unlike methods hitherto prominent in the literature. The method is applied to Czech data.
Keywords: D11; D12; 330; Consumer demand; unit values; Verbraucherausgaben; Nachfragesystem; Mikroökonomische Konsumfunktion; Tschechische Republik